Analysis of The Best Digital Tools That Benefit Education: A Systematic Review of The Literature - Jason Changanaqui-Morillas; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2021)
We live in a digital age, where education goes hand in hand with technology on its way to providing us with the means to access it. The following study aims to demonstrate the usefulness of digital tools in the knowledge environment. For the research, databases such as ScienceDirect, Scopus and ProQuest were consulted to search for articles. 50 scientific articles were obtained in the periods 2010 - 2020. The results showed Information and Communication Technologies (ICT) as the most used digital tool, with emphasis on social networks due to their ease and accessibility. There are even articles dedicated exclusively to them, with certain recommendations to be taken into account.
Keywords: Digital Tools; Benefit Education; Systematic Review.